Bouncing Regimes of Supercooled Water Droplets Impacting Superhydrophobic Surfaces with Controlled Temperature and Humidity - Guo, Chunfang (Langmuir : the ACS journal of surfaces and colloids, 2023)
Superhydrophobic surfaces have shown significant potential for the passive anti-icing application due to their unique water repellency. Reducing the contact time between the impacting droplets and the underlying surfaces with certain textures, especially applying the pancake bouncing mechanism, is expected to eliminate droplet icing upon impingement. However, the anti-icing performance of such superhydrophobic surfaces against the impact of supercooled water droplets has not yet been examined. Therefore, we fabricated a typical post-array superhydrophobic surface (PSHS) and a flat superhydrophobic surface (FSHS), to study the droplet impact dynamics on them with controlled temperature and humidity. The contact time and the bouncing behavior on these surfaces and their dependence on the surface temperature, Weber number, and surface frost were systematically investigated. The conventional rebound and full adhesion were observed on the FSHS, and the adhesion is mainly induced by the penetration of the droplet into the surface micro/nanostructures and the consequent Cassie-to-Wenzel transition. On the PSHS, four distinct regimes including pancake rebound, conventional rebound, partial rebound, and full adhesion were observed, where the contact time increases correspondingly. Over a certain Weber number range, the pancake rebound regime where the droplet bounces off the surface with a dramatically shortened contact time benefits the anti-icing performance. By further decreasing the surface temperature, the pancake rebound turns into the conventional rebound, where the droplet is not levitated after the capillary emptying process. Our scale analysis indicates that the frost between the posts reduces the capillary energy stored during the downward penetration, resulting in the failure of the pancake bouncing. A droplet adheres onto the frosted surface at sufficiently low temperature, especially at larger Weber numbers, on account of the coupling influence of droplet nucleation and wetting transition